Labor: Studies in Working-Class History - Labor and Working-Class History Associaiton (Labor: Studies in Working-Class History, 2003)
This journal is the official journal for the Labor and Working-Class History Association. The labor question—who will do the work and under what economic and political terms?—beckons today with renewed global urgency. As a site for both historical research and commentary, Labor hopes to provide scaffolding for understanding the roots of our current dilemmas. Although the tradition from which the journal derives its energy has focused primarily on social movements and institutions based on industrial labor, Labor intends to give equal attention to other labor systems and social contexts (agricultural work, slavery, unpaid and domestic labor, informal sector, the professions, etc.). Its focus begins on the US experience but extends to developments across the “American” hemisphere and to other transnational comparisons that shed light on the American experience.